(3QSGdI aj TQM GdebGdI GdeaQbIs - (3eLghds
(3ChdgG (B:s
(3GdMeO ddg GdbOje cdGeg GdYXje EfYGeg hGdUdGg Ydi eMeO NGJe GdQSGdI hHYO agPg QSGdI eYehdg ai TQM GdebGdI GdeaQbg ai JMbjb GdcdGe GdfaSi GdefShH Edi s
(3BNQgG (B:s
(3hEfeG LYd GddSGf Ydi GdaDGO OdjdkG djdG jdRe TF ef gPG hGdMeO ddg hMOg hUdi Ydi SjOfG eMeO hBdg hUMHI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQM s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs